Visual political communication in popular Chinese television series - Schneider, Florian (China Studies., 2012)
Television drama series are today the most popular format on Chinese TV. The fact that these series largely portray nationalist stories of glorious emperors and courageous officials leaves the impression that they must be propaganda, designed by the Communist Party. This volume challenges such assumptions and shows how TV drama production is a complex process of cultural governance that is not dominated by one particular actor, but characterized by diffuse political interests, commercial considerations, viewing habits, and ideological assumptions. By examining political discourses in Chinese drama series and analyzing the factors leading to their creation, this book explains why Chinese TV content relies so heavily on didactical messages and emotional symbols, and argues that such content risks creating precisely the kind of passive masses that Chinese media workers and government officials are trying so hard to emancipate.